Implementasi Asnaf Zakat dalam Pendistribusian Aset Zakat Berbasis Pemerataan dan Keadilan - Nasruddin Nasruddin; Nur Wahyu Ningsih; Weny Rosilawati (Jurnal Akuntansi dan Pajak, 2022)
The greatest development of zakat has been carried out during the development of Islam in Medina. At that time it was very varied, both in terms of purpose and form and has changed its orientation, from purely religious interests to the interests of the community. Therefore, the community at the time of the companions began to recognize the form of productive zakat, thus sparking the existence of zakat in its distribution directed at the productive sector. At that time the notion of productive zakat was more comprehensive, to develop the community's economy and the results of economic development, so that in the end the distribution of zakat assets was distributed for the socio-economic interests of the community. Indeed, the distribution of zakat assets is necessary, considering that the purpose of zakat is to improve the welfare of Muslims. In this case, the issue that is used as a reference in the professional management of zakat assets is the distribution of waqf assets based on equity and justice.